THE INTEGRATION OF ENGLISH INTO MYANMAR’S NATIONAL CURRICULUM: A CRITICAL REVIEW - Ana Mae Monteza (CV. Fahr Publishing, 2025)
This study investigates the structural and pedagogical challenges in integrating English into Myanmar's national curriculum by employing a longitudinal mixed-methods design. The research aims to explore how secondary school teachers across urban and rural contexts implement the communicative, integrated English curriculum, particularly through the lens of Technological Pedagogical Content Knowledge (TPACK). Data were collected over a one-year period through classroom observations, teacher interviews, student assessments, and policy document analysis. Findings reveal a significant gap between curriculum policy and classroom practice, largely influenced by limited teacher training, unequal access to technological resources, and disparities between urban and rural school settings. Despite curriculum reform initiatives promoting communicative competence and academic literacy, traditional teacher-centered approaches remain dominant. A key contribution of this research lies in its integration of TPACK and academic literacy into a holistic analytical model—rarely applied in Myanmar's multilingual and socioeconomically diverse context. The study further identifies inconsistencies in instructional materials and assessment practices across schools, underscoring the need for contextualized standardization. This research contributes a novel framework for English curriculum reform that connects national policy, teacher agency, and learner diversity, offering valuable insights for policymakers and education stakeholders in similar developing country settings. In conclusion, the study highlights that the success of English integration depends on systemic collaboration, continuous professional development, and adaptive policy implementation tailored to local contexts.